Evaluation of an obstetric and neonatal care upskilling program for community health workers in Papua New Guinea - Kamalini Lokuge; Freda Wemin; Grace Joshy; Glen DL Mola (BMC, 2024)
Abstract Background 60% of women in Papua New Guinea (PNG) give birth unsupervised and outside of a health facility, contributing to high national maternal and perinatal mortality rates. We evaluated a practical, hospital-based on-the-job training program implemented by local health authorities in PNG between 2013 and 2019 aimed at addressing this challenge by upskilling community health workers (CHWs) to provide quality maternal and newborn care in rural health facilities. Methods Two provinces, the Eastern Highlands and Simbu Provinces, were included in the study. In the Eastern Highlands Province, a baseline and end point skills assessment and post-training interviews 12 months after completion of the 2018 training were used to evaluate impacts on CHW knowledge, skills, and self-reported satisfaction with training. Quality and timeliness of referrals was assessed through data from the Eastern Highlands Province referral hospital registers. In Simbu Province, impacts of training on facility births, stillbirths and referrals were evaluated pre- and post-training retrospectively using routine health facility reporting data from 2012 to 2019, and negative binomial regression analysis adjusted for potential confounders and correlation of outcomes within facilities. Results The average knowledge score increased significantly, from 69.8% (95% CI:66.3-73.2%) at baseline, to 87.8% (95% CI:82.9-92.6%) following training for the 8 CHWs participating in Eastern Highlands Province training. CHWs reported increased confidence in their skills and ability to use referral networks. There were significant increases in referrals to the Eastern Highlands provincial hospital arriving in the second stage of labour but no significant difference in the 5 min Apgar score for children, pre and post training. Data on 11,345 births in participating facilities in Simbu Province showed that the number of births in participating rural health facilities more than doubled compared to prior to training, with the impact increasing over time after training (0-12 months after training: IRR 1.59, 95% CI: 1.04-2.44, p-value 0.033, > 12 months after training: IRR 2.46, 95% CI:1.37-4.41, p-value 0.003). There was no significant change in stillbirth or referral rates. Conclusions Our findings showed positive impacts of the upskilling program on CHW knowledge and practice of participants, facility births rates, and appropriateness of referrals, demonstrating its promise as a feasible intervention to improve uptake of maternal and newborn care services in rural and remote, low-resource settings within the resourcing available to local authorities. Larger-scale evaluations of a size adequately powered to ascertain impact of the intervention on stillbirth rates are warranted.